Administration for Developing Excellent Artistic Gymnastics as Perceived by Stakeholders - Soonchan, Rumpai; Supaporn, Salee; Phanwanich, Usakorn (Academic Journal of Thailand National Sports University, 2022)
The purpose of this study was to explore an administrative pattern for successful development of artistic gymnastics from steak holders’ perspective. Participants were 10 coaches, 10 athletes and 10 administrators who involved with artistic gymnastics sport. Data were collected through semi-structured interview, stimulated recall with photograph and concept mapping and were analyzed using a constant comparison. Trustworthiness was established using triangulation and prolonged engagement. Results indicated that in order to develop artistic gymnastics, three groups of steak holders namely coaches, athletes and administrators needed to be developed. Developing coaches included determining level of coaches, increasing numbers of coaches, improving capability of coaches and enhancing coaching experiences. Developing athletes involved increasing numbers of athletes, enhancing athletes’ ability and promoting their competitive experiences. Lastly, developing administrators included setting appropriate terms for being administrative committees of gymnastic association, seeking budget for purchasing equipment and providing fund for improving quality of coaches and athletes.